The fiddler - Lewis, Beverly (Minneapolis, Minn. : Bethany House, 2012)
"A wrong turn in a rainstorm leads Englisher Amelia Devries to Michael Hostetler, and the young Amishman's charming Old Order community of Hickory Hollow. Despite their very different backgrounds, Amelia and Michael both feel hemmed in by the expectations of others and struggle with how to find room for their own hopes. And what first seems to be a chance encounter might just change their lives forever"--P. [4] of cover.
Keywords: Man-woman relationships -- Fiction; Women violinists -- Fiction; Amish -- Fiction; Domestic fiction; Love stories; Christian fiction; Amish Country (Pa.) -- Fiction